Roman Ruins at Lincoln
The provision of sockets for timber beams shows how flooring was supported in a Roman building, setting the pattern for all the medieval building which was to follow. However, with the abandonment of Roman Britain in 406 A.D., there followed several centuries of strife. The centers of civilization were sacked and neglected, and for the second time the thread of architecture in this country broke.